The roles of tagging in the online curation of photographs. (April 2018) - Barton, David
Highlights: There are many reasons for tagging, not just the creation of taxonomies. Combines the detail of qualitative research with the breadth of quantitative. Corpus linguistics can support ethnographic insights. Analyses a dispute between users and platform owners. Uses the notion of curation to understand users' expectations. Abstract: This paper explores the variety of uses people make of the tagging feature on the photo-sharing site Flickr. The site developers intended uses are primarily to build a taxonomy to make the images on the site easily searchable. Data from examples of Flickr tags and interviews with selected users reveal that some tagging fits with this aim, whilst other uses challenge and subvert the intended uses. Tagging is used to do at least the following: identifying existing information in a photo; adding relevant new information; expressing affective stance towards the images; addressing specific audiences; making unrelated 'asides'; and for creative play. The discussion is then broadened by examining a dispute between Flickr and its users about changes being made to the site: this act as a 'telling case' (Mitchell, 1984) as people articulate what the site enables them to do and what it hinders. The dispute generated a thread of more than 29, 000 comments, making a corpus of 1, 774, 401 words. Using corpus linguistics tools the paper demonstrates how users contribute to curating this site, including their uses of tagging. Steps involved in curating the site are identified, including a focus on verbs of curation. Overall, the paper contributes to the analysis of a set of 'new' literacy practices and to understanding digital curation. The methods of the two studies reported here productively combine detailed methods of qualitative research with the breadth of quantitative analysis.